2020
DOI: 10.1249/mss.0000000000002295
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Loss as a Critical Variable Determining the Adaptations to Strength Training

Abstract: The results of the study are presented clearly, honestly, and without fabrication, falsification, or inappropriate data manipulation. The results of the present study do not constitute endorsement by the American College of Sports Medicine. This study has no conflicts of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
195
5
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(227 citation statements)
references
References 36 publications
17
195
5
10
Order By: Relevance
“…This study is an extension of our previous work (see Pareja-Blanco et al 21 ). However, no variables or training interventions described here have been reported previously.…”
Section: Subjectssupporting
confidence: 58%
See 3 more Smart Citations
“…This study is an extension of our previous work (see Pareja-Blanco et al 21 ). However, no variables or training interventions described here have been reported previously.…”
Section: Subjectssupporting
confidence: 58%
“…In agreement with our findings, previous VBT studies carried out using lower body exercises (ie squat) have shown that higher VL thresholds do not induce further 1RM strength gains than lower VL thresholds. 21,22,24 Moreover, all groups showed improvements in muscular endurance performance (ie FT-MNR and FT-AV), although the VL25 and VL50 groups attained the highest ES values. Supporting this finding, Izquierdo et al 29 observed greater BP muscular endurance following a training program to failure compared with non-failure training, although there were no differences in the squat exercise.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Velocity-based methods for prescription (i.e., load-manipulation [ 38 , 39 ] and volume control [ 40 ]), testing, and monitoring (i.e., load-velocity profiling [ 37 ]) are frequently applied to sport science support and research. Practitioners, therefore, must be confident in the technology they use to ensure effective implementation.…”
Section: Practical Applicationsmentioning
confidence: 99%